2011
DOI: 10.1007/s00431-010-1356-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, inflammatory, endothelial and haemostatic markers in a group of Italian obese children and adolescents

Abstract: Childhood obesity and its related comorbidities are increasingly recognised in children, predisposing them to early cardiovascular disease and metabolic syndrome. The objective of the study was to investigate markers of metabolism, inflammation and haemostasis in a group of Italian obese children and adolescents. Fifty-nine obese and 40 non-obese subjects were recruited. Fasting glucose and insulin, total cholesterol, HDL and LDL cholesterol, triglycerides, high-sensitivity C-reactive protein (hsCRP), tumour n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 31 publications
8
56
4
1
Order By: Relevance
“…D-dimers, fibrinogen, and vWFAg levels did not reach a significant correlation with vascular parameters. These results were in contrast with some previous literature studies, 11,[49][50][51][52] which reported the influence of such parameters on endothelial function and on vascular wall morphological structure. In fact, OrenesPiñero et al 53) pointed out the correlation between BMI and coagulation parameters, observing an increased prothrombotic status in adult subjects suffering from increased body weight.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…D-dimers, fibrinogen, and vWFAg levels did not reach a significant correlation with vascular parameters. These results were in contrast with some previous literature studies, 11,[49][50][51][52] which reported the influence of such parameters on endothelial function and on vascular wall morphological structure. In fact, OrenesPiñero et al 53) pointed out the correlation between BMI and coagulation parameters, observing an increased prothrombotic status in adult subjects suffering from increased body weight.…”
Section: Discussioncontrasting
confidence: 99%
“…Adiponectin protein is probably an insulin modulator and plays a protective role against inflammation and atherosclerosis, stimulating the production of endothelial nitric oxide and inhibiting the accumulation of lipids in macrophages [7][8][9][10] . Several studies showed that hypoadiponectinemia is associated with greater BMI, waist circumference, and insulin resistance in obese children 11,12) . High molecular weight adiponectin acts on cardiac muscular cells protecting them from ischemia/ reperfusion damages by improving cyclooxygenases-2 activity and promoting nitric oxide (NO) production; it obstacles the promotion of cardiac fibrosis and the morphological and structural alterations derived from hypertrophic stimuli, while it ameliorates contractile function by inducing calcium influx into myotubes.…”
Section: Haemostatic Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise not all obese persons will develop IR, endothelial dysfunction, MS and cardiometabolic diseases, and paradoxically, a high number of non-obese individuals do suffer from these conditions [30]. A number of biomarkers described in literature, such as highmolecular weight subfraction of adiponectin, tumour necrosis factor alpha (TNF-), plasminogen activator inhibitor 1 (PAI-1), von Willebrand Factor (vWF), cytokines related to IR, inflammation, atherosclerosis, type 2 diabetes, dyslipidemia and hypertension [30][31][32] are not available for clinical practice. Furthermore the measurement of small low-LDL-C (phenotype B), which is associated with a fourfold atherogenic risk [33], or even insulin dosage that is closely related to IR are difficult to measure.…”
Section: Discussionmentioning
confidence: 99%